Transforming Feather Meal Into a High‐Performance Feed for Broilers - Mandana Salehizadeh; Maryam Tajabadi Ebrahimi; Seyed Naser Mousavi; Abbas Akhavan Sepahi; Reza Orooji (Veterinary Medicine and Science)
ABSTRACT Background The poultry industry faces challenges with the high cost and environmental impact of Soybean meal. Feather meal, a byproduct with low digestibility due to its keratin content, is a potential alternative. Recent biotechnological advances, including enzymatic and bacterial hydrolysis, have enhanced its digestibility and nutritional value. Objective This study aimed to evaluate and compare the efficacy of three different feather meal processing methods as partial replacements for soybean meal in broiler diets. The methods assessed included hydrolyzed feather meal treated with Streptomyces bacteria, commercial enzyme‐treated feather meal, and boiled feather meal. Their effects on performance and nutrient digestibility were evaluated in Ross 308 male broiler chickens. Materials The study involved 525 Ross 308 male broiler chickens were allocated to seven dietary treatments, which included a control diet and varying combinations of feather meal and soybean meal. Streptomyces sp. MSM5 was shown to effectively produce keratinase, enhancing the amino acid content of the feather meal. Results Birds fed diets containing 33% and 67% boiled feather meal exhibited significantly reduced body weight gain (BWG) and increased feed conversion ratio (FCR) compared to the control group (p < 0.05). In contrast, birds fed diets with 33% hydrolyzed feather meal, treated with either enzymes or bacteria, showed similar BWG and FCR to those on the control diet. However, diets with 67% hydrolyzed feather meal led to significant reductions in performance (p < 0.05). Additionally, diets containing 33% and 67% boiled feather meal, as well as 67% hydrolyzed feather meal, resulted in significantly lower carcass percentage, breast muscle percentage, thigh muscle percentage, overall dry matter digestibility, and protein digestibility (p < 0.05). Conclusion The results indicate that substituting as much as 33% of soybean meal with processed feather meal, particularly when treated with enzymes or bacteria, does not negatively impact broiler performance. Furthermore, the results underscore the potential of biotechnological treatments, such as bacterial keratin hydrolysis, to enhance the nutritional value of feather meal, transforming it into a high‐quality, sustainable protein source for the poultry industry.